Impact of Sodium Butyrate Treatment in LPS-Stimulated Peripheral Blood Mononuclear Cells of Poorly Controlled Type 2 DM - Wibowo, Heri; Harbuwono, Dante S.; Tahapary, Dicky L.; Kartika, Rona; Pradipta, Saraswati; Larasati, Rahma A. (Frontiers in Endocrinology, 2021)
Type 2 diabetes mellitus (T2DM) is associated with chronic low-grade inflammation, which is marked by the dysregulation of innate and adaptive immune responses. Therefore, reducing inflammation, possibly through an immunoregulatory agent, may play a role in T2DM treatment. Butyrate is the most potent short-chain fatty acid (SCFA), and it exerts anti-inflammatory properties by inhibiting histone deacetylase activity. As an immunoregulatory agent, sodium butyrate can inhibit nuclear factor kB (NF-kB) activation and reduce the production of pro-inflammatory cytokines in immune cells. The aim of the study was to measure the level of plasma butyrate in poorly controlled T2DM and normoglycemic participants and to compare the response of peripheral blood mononuclear cells (PBMCs) to sodium butyrate treatment between the groups by measuring production of the following cytokines: tumor necrosis factor (TNF)-α, interleukin (IL)-6, interferon (IFN)-γ, IL-13, and IL-10. The in vitro study examined the PBMCs of 15 participants with poorly controlled T2DM and 15 normoglycemic participants. PBMCs were cultured with the following stimulations for two days at a temperature of 37°C and 5% CO2: 100 ng/mL lipopolysaccharide (LPS), 1 mM sodium butyrate, or a combination of 100 ng/mL LPS and 1 mM sodium butyrate. Plasma butyrate was measured using gas chromatography-mass spectrometry, and cytokines from culture supernatant were analyzed using magnetic beads multiplex assay. Plasma butyrate levels in participants with poorly controlled T2DM did not significantly differ from those in normoglycemic participants (p = 0.105). Compared to treatment with an LPS-stimulated PBMC culture, treatment with 1 mM sodium butyrate reduced the levels of TNF-α (p < 0.039) and IFN-γ (p < 0.038) in normoglycemic participants. The same general trend was seen in PBMC from participants with poorly controlled T2DM, but higher variability appeared to preclude statistical significance. These data suggest that butyrate may modulate inflammatory cytokine production in human PBMCs but more research is needed to determine if butyrate is anti-inflammatory in poorly controlled T2DM.